2020
DOI: 10.1111/jocs.14939
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve predictors for minimally invasive mitral valve surgery; how far should the rabbit hole go?

Abstract: Objective: To analyze predictors that influence the learning curve of minimally invasive mitral valve surgery (MIMVS). Methods: Patients who underwent MIMVS between March 2010 to March 2015 were retrospectively analyzed. Predictive factors that influence the learning curve were analyzed. Results: One hundred and five patients were included in the analysis. Cardiopulmonary bypass (CPB) time in minutes was 158.72 ± 40.98 and the aortic crossclamp (ACC) time in minutes was 114.48 ± 27.29. There were three operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The CUSUM curve showed an upward slope when the operation time exceeded the mean value, and conversely, the CUSUM curve showed a downward slope. In this study, the CUSUM learning curve underwent a significant upward trend before the 75th surgery, and significant improvements in both AC and CPB were observed after the 75th surgery, which was similar to the results of previous learning curve studies of minimally invasive valve surgery, Although there were significant differences between different studies, the overall tendency of change in CUSUM was similar, with the number of procedures required to overcome the learning curve ranging from 64 to 116 [20][21][22] . However, learning curve outcomes may vary considerably between different minimally invasive valve procedures, with parasternal, hemi-sternotomy, and mini-thoracotomy approaches likely to reach plateau more rapidly, and correspondingly, totally robotic approaches, and totally endoscopic approach may require more time and training to achieve stability.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The CUSUM curve showed an upward slope when the operation time exceeded the mean value, and conversely, the CUSUM curve showed a downward slope. In this study, the CUSUM learning curve underwent a significant upward trend before the 75th surgery, and significant improvements in both AC and CPB were observed after the 75th surgery, which was similar to the results of previous learning curve studies of minimally invasive valve surgery, Although there were significant differences between different studies, the overall tendency of change in CUSUM was similar, with the number of procedures required to overcome the learning curve ranging from 64 to 116 [20][21][22] . However, learning curve outcomes may vary considerably between different minimally invasive valve procedures, with parasternal, hemi-sternotomy, and mini-thoracotomy approaches likely to reach plateau more rapidly, and correspondingly, totally robotic approaches, and totally endoscopic approach may require more time and training to achieve stability.…”
Section: Discussionsupporting
confidence: 87%
“…However, learning curve outcomes may vary considerably between different minimally invasive valve procedures, with parasternal, hemi-sternotomy, and mini-thoracotomy approaches likely to reach plateau more rapidly, and correspondingly, totally robotic approaches, and totally endoscopic approach may require more time and training to achieve stability. However, previous studies related to learning curves of minimally invasive mitral valve repair have not performed more precise subgroup analyses according to the different procedures and did not make strict exclusions for simultaneous procedures, because any simultaneous procedure may result in prolonged AC and CPB times [21][22][23][24] . In this study, the CUSUM of postoperative adverse events could not be visualized due to the low incidence, but according to previous literature, the incidence of postope-rative complications was similar between total thoracoscopic MVP and conventional MVP surgery 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified that total thoracoscopic MVP provided equally satisfactory surgical results compared to conventional MVP and that stabilization could be achieved gradually after completion of the 75th procedure, which was similar to the results of previous learning curve studies of minimally invasive valve surgery. Although there were significant differences between different studies, the overall tendency of change in CUSUM was similar, with the number of total thoracoscopic MVPs required to overcome the learning curve ranging from 64 to 116 [13][14][15] . However, we failed to perform an assessment of the learning curve of CUSUM (Cumulative Sum) based on total thoracoscopic AVR due to the insufficient number.…”
Section: Discussionmentioning
confidence: 90%
“…The gradient of the learning curve required for implementing the MIVS approach is a controversially discussed topic and influenced by many factors such as individual operative times and frequency of procedures [18]. Additionally, adequate patient selection seems to be an important factor for the success of less-experienced surgeons regarding the outcome [19].…”
Section: Discussionmentioning
confidence: 99%
“…Irrespectively of the approach, guidelines recommend referral to mitral valve reference centers for complex repairs [21]. As other single-center studies show that MIVS and MVR can be learned safely with satisfying short- and long-term results [19, 22, 23] – with an increasing demand of minimally invasive cardiac surgery at the same time – we should focus on creating a bigger availability of MIVS and MVR in the future.…”
Section: Discussionmentioning
confidence: 99%